2017
DOI: 10.1016/j.anucene.2016.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Assembly-level analysis of heterogeneous Th–Pu PWR fuel

Abstract: This study compares homogeneous and heterogeneous thorium-plutonium (Th-Pu) fuel assemblies (with high Pu content-20 wt%), and examines whether there is an increase in Pu incineration in the latter. A seed-blanket configuration based on the Radkowsky thorium reactor concept is used for the heterogeneous assembly. This separates the thorium blanket from the uranium seed, or in this case a plutonium seed. The seed supplies neutrons to the subcritical thorium blanket which encourages the in-situ breeding and burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…While there are notable downsides to the Th-fuel cycle, specifically the lack of commercial infrastructure and the reduced worth of certain control materials (du Toit & Naicker, 2018) (Alhaj, et al, 2016) (Lau, et al, 2014) (Insulander Bjork, et al, 2013 (Fridman & Kliem, 2011) (Lamarsh & Baratta, 2001), it may warrant further investigation. Th-Pu only recycle has been studied in depth (Zainuddin, et al, 2017) (Alhaj, et al, 2016) (Zainuddin, et al, 2016) (Tucker, et al, 2015) (Yun, et al, 2010) (Mittag & Kleim, 2011) (Schram & Klaassen, 2007) (Sorensen, et al, 2006) (Kim & Downar, 2002) (Galperin, et al, 2000). However, it is Th-Pu-MA recycle that is of more interest with respect to UK Pu management due to the previously mentioned build-up of Am241.…”
Section: Viable Technologies For Pu Dispositionmentioning
confidence: 99%
“…While there are notable downsides to the Th-fuel cycle, specifically the lack of commercial infrastructure and the reduced worth of certain control materials (du Toit & Naicker, 2018) (Alhaj, et al, 2016) (Lau, et al, 2014) (Insulander Bjork, et al, 2013 (Fridman & Kliem, 2011) (Lamarsh & Baratta, 2001), it may warrant further investigation. Th-Pu only recycle has been studied in depth (Zainuddin, et al, 2017) (Alhaj, et al, 2016) (Zainuddin, et al, 2016) (Tucker, et al, 2015) (Yun, et al, 2010) (Mittag & Kleim, 2011) (Schram & Klaassen, 2007) (Sorensen, et al, 2006) (Kim & Downar, 2002) (Galperin, et al, 2000). However, it is Th-Pu-MA recycle that is of more interest with respect to UK Pu management due to the previously mentioned build-up of Am241.…”
Section: Viable Technologies For Pu Dispositionmentioning
confidence: 99%
“…Past studies prove a superior incineration of plutonium on thorium/plutonium seed‐blanket configurations, compared to the traditional MOX fuel in PWR . Recently, a comparison analysis between homogeneous and heterogeneous thorium/plutonium fuel assemblies (with high Pu content‐20 wt%) was conducted by Zainuddin et al It was found that the homogeneous fuel with and without burnable poisons could achieve much higher plutonium incinerations than heterogeneous fuel configurations, and could still attain a reasonably high discharge burnup.…”
Section: Introductionmentioning
confidence: 99%